2012
DOI: 10.1038/ncomms2273
|View full text |Cite
|
Sign up to set email alerts
|

Sub-resolution lipid domains exist in the plasma membrane and regulate protein diffusion and distribution

Abstract: Lipid microdomains are postulated to regulate many membrane-associated processes but have remained highly controversial. Here we provide the first direct evidence that the plasma membrane of intact, live cells is comprised of a sub-resolution mixture of approximately 76% ordered and 24% disordered lipid domains, which correspond to liquid-ordered and -disordered model membranes. These measurements were based on the unmixing of fluorescence lifetime decays (phasor analysis) obtained from environmentally sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
206
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(219 citation statements)
references
References 48 publications
11
206
1
1
Order By: Relevance
“…However, lipid domains may not be static entities but constantly reshaped in membranes that exhibit lipid phase separation (65). Indeed, it may be the ability to reorganize the plasma membrane upon TCR triggering, and not the basal membrane order and composition per se, that is functionally important for downstream activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, lipid domains may not be static entities but constantly reshaped in membranes that exhibit lipid phase separation (65). Indeed, it may be the ability to reorganize the plasma membrane upon TCR triggering, and not the basal membrane order and composition per se, that is functionally important for downstream activation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some controversy surrounding their existence (74), the presence of ordered (Lo) cholesterol-rich lipid domains in cell membranes has been strongly supported by several recent studies (75,76). Such microdomains may play essential roles in the spatial organization and localization of plasma membrane components.…”
Section: Discussionmentioning
confidence: 99%
“…As a final way of experimentally validating our flicker approach, we investigated use of 7-ketocholesterol (7-KC), a probe that reduces lipid packing and lipid order by integrating into the RBC membrane (36). We found that 7-KC significantly and specifically reduces bending modulus without affecting tension properties (Fig.…”
Section: Eba175mentioning
confidence: 99%